In vitro and in silico interaction of porcine α-amylase with Vicia faba crude seed extract and evaluation of antidiabetic activity. Issue 4 (4th July 2017) - Choudhary, Dhiraj Kumar; Mishra, Abha
ABSTRACT: Diabetes mellitus is a group of metabolic disorder of glucose metabolism. The proper management of blood glucose level is an indicator in the treatment of this complex pathology. The aim of the present study was to evaluate the inhibitory potential of Vicia faba crude seed extracts on the activities of α-amylase. Phytochemical screening, FTIR and HPLC analysis confirmed the presence of a phenolic compound with percentage yield of 9.87% in the acetone extract. Acetone extract of seed had highest inhibitory potential against porcine α-amylase (IC50 value of 2.94 mg/mL). Kinetic analysis revealed that the acetone and methanol extract displayed mixed mode of inhibition toward α-amylase. In-silico analysis was agreement with in-vitro studies in which phenolic compounds (catechin, epicatechin, gallic acid, and proanthocyanidin) showed more negative free energy against standard drug (acarbose) and bound with catalytic residues of α-amylase. These results might be due to the synergistic action of constituents present in seed extract or acting separately.